A Steroidal Molecular Rotor with Fast Solid‐State Dynamics Obtained by Crystal Engineering: Role of the Polarity of the Stator. Issue 38 (6th July 2022) - Labra‐Vázquez, Pablo; Ochoa, María E.; Alfonso‐Herrera, Luis A.; Vera, Marco A.; Farfán, Norberto; Santillan, Rosa
Abstract: A set of Steroidal Molecular Rotors (SMRs) were synthesized and characterized employing a Sonogashira cross‐coupling reaction as the key synthetic step. The static dipole moment (μ0 ) of the stator was examined as a crystal engineering criterium that could determine the easiness with which the rotator participates in the high energy supramolecular interactions that frequently preclude rotation in this class of molecular machines. The strategy is critically evaluated through theoretical/experimental analyses, featuring SXRD experiments and QM/MM computations of the rotational activation energy ( Ea ), allowing us to propose, within the systems studied, a potential correlation between the use of stators with lower μ0 and a lowering of the Ea value. Results from solid‐state NMR revealed that one of the most promising compounds indeed hosts fast rotational motion (above 25–30 kHz), standing as a rare example of a SMR with fast rotation within a crowded crystallographic environment. Abstract : A theoretical/experimental study is presented for a set of Steroidal Molecular Rotors (SMRs). Extensive DFT computations and SXRD experiments revealed a potential correlation between the polarity of the stator and the rotational activation energy. Following this crystal engineering criterium we report a rare example of a SMR with fast rotational dynamics in spite of featuring a crystallographically crowded rotator.